A dynamic simulator for strategic management in service sector - Çırak, Korkut. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1999., 1999)
The main objective of this research is to construct an interactive dynamic simulation model on which the strategic management of an insurance company, concerning the interactions between the technical departments of the company, those between the company and the market and the related strategic decisions can be analyzed and certain policies for sustaining growth can be tested. More specifically, the model focuses on long-term, strategic management problems that are naturally dynamic and persistent. The model generates many performance measures concerning the financial, technical and market aspects. In order to construct such a simulation game, a system dynamics model of the strategic management aspects of an insurance company is built. The model is validated and verified by standard tests. Next, the necessary changes are made on the model to construct the interactive gaming version of it. After the validation of the game, it is played by different players with academic and business backgrounds. Finally the game results of these players are analyzed and compared. The outputs provided by the players show different difficulties involved in managing the growth of an insurance company successfully. In conclusion, the simulation game provides a research platform for the theory of strategic decision making as well as a learning laboratory for the practice of scientific management education.
Keywords: Service industries -- Management.; Strategic planning -- Simulation methods.; Management -- Simulation methods.; Insurance companies -- Management -- Simulation methods.